ANALYSIS OF THE IMPLEMENTATION OF THE EXPENDITURE ESTIMATES OF BUDGETARY INSTITUTIONS AS A TOOL FOR IMPROVING THE EFFICIENCY OF PUBLIC FINANCE MANAGEMENT - Копчикова, І.В.; Кудирко, О.М. (SWorldJournal, 2025)
The article is devoted to the study of the features of the analysis of the execution of expenditure estimates in budgetary institutions as an important tool for managing public finances. The authors emphasize that the effective use of budget funds is the